Retrospective study in 23 patients of the self-expanding Sinus-XL Stent for treatment of malignant superior vena cava obstruction caused by non-small cell lung cancer - Mokry, Theresa; Bellemann, Nadine; Sommer, Christof-Matthias; Heußel, Claus Peter; Bozorgmehr, Farastuk; Gnutzmann, Daniel; Kortes, Nikolas; Kauczor, Hans-Ulrich; Radeleff, Boris; Stampfl, Ulrike (Journal of vascular and interventional radiology, 2015)
Purpose - To evaluate retrospectively the self-expanding nitinol Sinus-XL stent (OptiMed, Ettlingen, Germany) for the treatment of superior vena cava (SVC) obstruction caused by non-small cell lung cancer (NSCLC). - Materials and Methods - Between October 2009 and December 2012, 23 patients (7 women and 16 men; age, 62.5 y ± 8.5) with stage IIIA (1 patient), IIIB (4 patients) or IV (18 patients) NSCLC and acute SVC obstruction were scheduled for urgent stent implantation. The primary study endpoints were technical success (defined as accurate stent placement with complete coverage of the obstructed SVC), residual stenosis < 30%, and clinical efficacy. Complications were assessed as a secondary study endpoint. - Results - There were 26 stents implanted in 23 patients. The technical success was 100%. Stent dilation was performed after deployment in 18 cases (78%). Stent migration into the right atrium occurred immediately after deployment in one patient; however, this stent was successfully repositioned and stabilized by a second stent. The clinical symptoms improved at least one category according to the International Consensus Committee on Chronic Venous Disease after stent implantation in all but one patient. The mean clinical follow-up was 66 days ± 83 (range, 1-305 d). Three minor complications (13%) and one major complication (4%) occurred. - Conclusions - Implantation of the self-expanding Sinus-XL stent for treatment of SVC obstruction caused by NSCLC is a safe and effective urgent treatment in this palliative setting.
Gesehen am 12.06.2020